확정급여형 퇴직급여채무 대비 연금자산의 적립수준이 회사채 신용등급에 미치는 영향 - 최종서(Jong-seo Choi); 노정희(Jung-hee Noh) (한국증권학회지, 2017)
본 연구는 확정급여형 퇴직급여제도를 채택한 기업을 대상으로 퇴직급여채무 대비 연금자산의적립수준이 회사채 신용등급에 미치는 영향에 대하여 검증한 연구이다. 근로자퇴직급여보장법에서는퇴직급여채무 대비 연금자산이 법적으로 권고하는 최소수준에 미달하여 적립될 경우, 3년 이내 이를해소할 것을 요구하고 있다. 또한 근로기준법과 근로자퇴직급여보장법에서는 임금채권과 퇴직금채권이다른 채권에 비해 우선적으로 변제되도록 규정하고 있다. 즉 기업의 도산이나 파산 시 다른 채권에비해 퇴직급여채권이 1순위로 변제되므로 퇴직급여채무와 적립수준에 관한 회계정보는 채권투자자들의 의사결정과정에 상당한 영향을 미칠 수 있다. 실증분석 결과 당기의 퇴직급여채무 대비 연금자산의 적립수준이 높을수록 차기의 회사채 신용등급은 낮은 경향이 확인되었다. 또한 적립수준이전년도 대비 감소하는 기업일수록 다음해에 회사채 신용등급이 하향조정 되는 경향도 확인되었다. 게다가 이러한 효과는 근로자퇴직급여보장법에서 요구하는 최소적립수준에 미달하는 과소적립기업들에게서만 관찰되어 퇴직급여 지급재원의 과소적립과 과대적립이 회사채 신용등급에 미치는 영향은비대칭적인 것으로 나타났다. This study investigates whether funding level of defined benefit pension liabilities affects corporate bond ratings. In order to pursue the research objective, we collect 3,194 firm-year observations of non-financial companies listed in the KRX which adopted DB pension plans over the period of 2005 to 2014. We employ ordered probit model for test purpose whereby corporate credit ratings are regressed on pension funding levels and control variables. We also use ordinary least square analysis to examine whether the magnitude of funding level changes is associated with the bond rating changes. According to the Guarantee of Workers’ Retirement Benefit Act (Article 16), firms with DB pension plans shall maintain the ability to pay the benefits. In order to secure such ability, employers are required to maintain “minimum level of reserve” at the end of each fiscal year. If the reserve balance proves to be less than the required minimum level at any fiscal year end, employers should make up for the deficiency in the following 3 years. The replenishment process has a direct impact on the company’s internal cash resources. Moreover, pension liabilities shall be paid in preference to taxes, public charges and other claims. When a firm goes into bankruptcy, unfunded pension liabilities are senior to secured or unsecured bond payments. As such, the claim of unfunded pension obligations could potentially reduce the future payoff to other bondholders, resulting in lower credit ratings. Consistent with expectations, our findings suggest that low pension funding level tends to decrease bond’s credit rating. In addition, an improvement or deterioration of pension funding levels is associated with bond rating changes. We find that this relationship is more pronounced for under-funded firms, whose reserve balance is below the required minimum level. This study is, to our knowledge, among the first research endeavors undertaken to examine the effects of unfunded pension liabilities on corporate bond credit ratings in Korean capital market context. Notably in this paper, we document the asymmetric relationship between the funding level of DB pension plans and corporate credit ratings. The results of this study is expected to provide practical implications to corporate bond investors and contribute to rational decision making by capital market participants. KCI Citation Count: 7